On Seeking to Improve IMF Conditionality - Williamson, John (American Economic Review, 2016)
ing the International Monetary Fund (IMF) lend to its member countries? At a somewhat abstract level, I would suggest that it could be defined as that of easing the external constraint on its member countries to the extent that such an easing can be expected to be advantageous to the world community as a whole. It follows immediately that the eas- ing has to be of the external constraint pro- vided by liquidity rather than solvency, since at best, an easing of the solvency constraint involves a resource transfer that will leave the donors worse off, while at worst, a belief in endogeneity of the solvency constraint creates moral hazard problems that under- mine the incentive for economic efficiency. Hence, my conception of the principle that should be guiding the Fund's lending policies is that they ease the external liquidity con- straint to the degree that is generally ad- vantageous while preserving the intertem-